Target Engagement in Lead Generation. Issue 5 (1st March 2015) - Durham, Timothy B.; Blanco, Maria-Jesus
Graphical abstract: Abstract: The pharmaceutical industry is currently facing multiple challenges, in particular the low number of new drug approvals in spite of the high level of R&D investment. In order to improve target selection and assess properly the clinical hypothesis, it is important to start building an integrated drug discovery approach during Lead Generation. This should include special emphasis on evaluating target engagement in the target tissue and linking preclinical to clinical readouts. In this review, we would like to illustrate several strategies and technologies for assessing target engagement and the value of its application to medicinal chemistry efforts.